Developmental Process of Critical Reading Proficiency of Iranian Agricultural Engineering Students in EAP - Maria Shobeiry, (International Journal of Psychosocial Rehabilitation, 2026)
Iranian students come from a cultural background in which critical thinking is not of high importance therefore they usually face difficulty in EAP courses in western universities. This research is a case study to investigate the developmental process of critical reading skill of three Iranian agricultural engineering master students during 21-weeks of an EAP course within the framework of Davies and Barnett (2015) and Blooms' (1956) taxonomy of critical thinking and pedagogy. The participants' answers to the Bloom's chart of critical thinking, voice recordings of the sessions, and my own observation notes were used as the data which was descriptively analyzed from critical skill, criticality, and critical pedagogy perspective. The results revealed that the first critical cognitive skills developed in the participants included interpreting, making inferences, and predicting the main ideas. The next critical skills that developed included analyzing causal relationships and synthesizing claims based on the students' own frameworks. Not developing critical character at the same pace as critical skills proved that developing criticality needs more practice and time allocation in EAP programs. Moreover, the ability to engage actively with reading materials, critical pedagogy perspective, did not develop as thriving as the critical skills and criticality in the participants.